2005
DOI: 10.1063/1.1848192
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon resonance assisted huge nonlinear refraction and absorption in ZnO thin films

Abstract: Optical nonlinearities of ZnO thin films, made by laser deposition, were investigated by the Z-scan method using a mode-locked femtosecond Ti:sapphire laser. The measured bound-electron nonlinear index of refraction ␥ and the two-photon absorption coefficient ␤ at near-IR wavelengths show an enormous enhancement compared with measurements on bulk ZnO at 532 nm. The results reveal that two-photon resonance to the band edge and exciton energy level is responsible for the nonlinear absorption and that the free ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 22 publications
1
51
0
3
Order By: Relevance
“…revealed that ZnO gas sensors could respond to the visible light [1] produced by the two-photon excitation process [11,12] so that the visible light can be used as an excitation source. C.…”
Section: Photo-generated Free Charge Carriers In Lightenhanced Metal mentioning
confidence: 99%
“…revealed that ZnO gas sensors could respond to the visible light [1] produced by the two-photon excitation process [11,12] so that the visible light can be used as an excitation source. C.…”
Section: Photo-generated Free Charge Carriers In Lightenhanced Metal mentioning
confidence: 99%
“…This transition produces electron-hole pairs in the excited states and, subsequently, the band-edge emission via their radiative recombination [9]. The two photon absorption (2PA) in semiconductor nanocrystals (NCs) has been widely investigated [8,10], while the research effort on their three-photon absorption (3PA) is limited [11]. The three photon absorption was observed in ZnO and ZnS crystals when pump with lasers of ultra excitation irradiance which was more than 40 GW/cm 2 [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The optical and electrical properties of ZnO nanostructures are studied at different preparation techniques and at different substrate materials [5,6]. The pumping of ZnO crystalline nanofilm with near-infrared femtosecond radiation pulses, enhances the nonlinear interaction between the ultrahigh intensity applied optical field and the ZnO nanostructures [7,8]. The nonlinear interaction leads to the simultaneous absorption of two or more photons of subband gap energy.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The nonlinear optical responses of ZnO were investigated to better understand the nonlinear optical properties, such as secondharmonic generation (SHG) and third-harmonic generation (THG). [4][5][6][7][8][9] The non-resonant two-photon absorption (2PA) and three-photon absorption (3PA) processes were also examined by monitoring the multiphoton-induced photoluminescence. 4,10 However, there are few reports on the simultaneous measurements of harmonic generation (SHG and THG) and multiphoton absorption (2PA and 3PA), 4,11 although the competition between them is important for potential applications.…”
mentioning
confidence: 99%